Competency Based Training Of Undergraduate Medical Students On Papanicolaou Test (pap) Smear (Indian Journal of Applied-Basic Medical Sciences, 2022)
Background: Cervical cancer is one of the most preventable of all cancers and is the second leading cause of death from malignancy amongst female patients. Utilizing Pap test for early detection of carcinoma cervix by all graduating medical students would be an excellent preventive strategy. The current modes of teaching medical students (lecture-based curricula) neither encourage the right qualities in students nor impart a life-long respect for learning.Objective: At the end of the training, the undergraduate students would become competent in learning about Pap smear with the help of The Pap smear teaching cum testing module (brief lectures + hands on training). Methods: Following approval by the Institutional Ethics Committee (IEC), the training was divided into theory, practical and demonstration classes, lasting from October 2014 to March 2015. Subjects included 50 students of 3rd MBBS. Pretest were conducted and results were evaluated and tabulated on excel sheet. The students were initiated into clinical application of Pap smear on ZOE model, through demonstration and skill practice under the supervision of trained faculty. Students were asked for their feedback to the questionnaire provided to them. Post-test in the form of a MCQ test, short answer-question was taken for evaluation of theoretical knowledge, scientific principles and application. Practical skills were evaluated based on practice session on ZOE model, assessed on adherence to DOPS checklist for Pap smear, the results were formulated. Student paired t test was performed to compare the scores of the pretest and post-test sessions.Results: Students showed improvement in post-test compared to the pretest. Feedbacks showed that students were enthusiastic in this innovative way of teaching and expressed their satisfaction. 90% students agreed that competency-based training of Pap smear made them understand the steps and made them confident about carrying out the procedure. Practical assessment was done on ZOE model with DOPS Checklist, 80% students’ demonstrated proficiency in practical skills by scoring 100% in checklist adherence. Conclusion: Interactive-competency-based teaching module among the small group in addition to the didactic lectures can improve the performance of the students and make them better to understand the subject better with lasting effect.
Keywords: PAP smear; Competency; training; undergraduate medical students